Utilization of the major criterion’s method for solving of the signal restoring problem - Баранов, В. Л.; Жуков, І. А.; Засядько, А. А. (Proceedings of National Aviation University (archive), 2003)
Theoretical and practical researches which are presented in this work have shown the similarity of the major criterion method to the Tikhonov’s method in solving ill-prosed problems of the signals regeneration by properties. The main features are: the sensitivity of solution to finding regularization parameter, stability to signals measurement errors, convergence of the calculations process. The advantage of the major criterion method over the Tikhonov’s method is in simple finding regularization’s parameter